The Securitisation of Conflict-Related Sexual Violence in the United Nations Women, Peace and Security Agenda: The Case of Liberia, 2000-2013 - Garach, Ushna (Department of Political Studies, 2024)
This thesis explores the securitisation of sexual violence in the United Nations Women, Peace and Security agenda, drawing on the Liberian experience. This study is conducted through a critical discourse analysis of the resolutions adopted by the United Nations Security Council from 2000 to 2019, and the Liberian National Action Plan, implemented from 2009 to 2013 as a tool to localise the Women, Peace and Security Agenda in Liberia. Four categories of analysis have been developed as a limited perspective of the securitisation of sexual violence: women and girls as victims and in need of protection; men and boys as victims; special attention to sexual violence and rape; and sexual violence as a threat to international peace and security. This thesis aims to investigate the securitisation of sexual violence and its influence on the response to sexual violence in the Liberian National Action Plan. Ultimately, this thesis finds that the Women, Peace and Security agenda has facilitated the securitisation of sexual violence through: the overrepresentation of women and girls as victims in need of protection; a corresponding underrepresentation of men and boys as victims; and a consistent depiction of sexual violence as both the most egregious type of violence and as an impediment to international peace and security. Its influence on the Liberian National Action Plan is limited, indicated by a sense of agency assigned to women and girls through the specification of the types of protection from which they would benefit; the inclusion of men (though boys are not mentioned) as beneficiaries of anti-sexual and gender-based violence measures; the inconsistent depiction of the comparable severity between sexual violence and other forms of violence; and no mention of sexual violence as a threat to international peace and security. This thesis provides a limited insight of the extent to which norms institutionalised by the United Nations occur in localised tools.